Pirates don't wear pink sunglasses - Dadey, Debbie; Jones, Marcia Thornton; Gurney, John; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1994)
Suspense, humor, and the appealing Bailey School kids make this an irresistible early chapter book. At Camp Lone Wolf, the Bailey kids suspect that the camp director is a werewolf. What's more, the newest member of the camp staff, Captain Teach, thinks he's a pirate. Line drawings.
"A Little Apple paperback."
G4
Keywords: Bailey School kids (Fictitious characters) -- Juvenile fiction; Pirates -- Juvenile fiction; Humorous stories